(5x-7)=(3x+17)

Simple and best practice solution for (5x-7)=(3x+17) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x-7)=(3x+17) equation:



(5x-7)=(3x+17)
We move all terms to the left:
(5x-7)-((3x+17))=0
We get rid of parentheses
5x-((3x+17))-7=0
We calculate terms in parentheses: -((3x+17)), so:
(3x+17)
We get rid of parentheses
3x+17
Back to the equation:
-(3x+17)
We get rid of parentheses
5x-3x-17-7=0
We add all the numbers together, and all the variables
2x-24=0
We move all terms containing x to the left, all other terms to the right
2x=24
x=24/2
x=12

See similar equations:

| 2n-6=9n+8 | | 0.6y+2=1.2y-4 | | -3/4x+8=-5/4x+15 | | c=19 | | 0.8y+3=1.4y-12 | | y+14=22 | | p+23=86 | | ?x.50=1000 | | z-32=34 | | (10x-30)=(6x+6)=180 | | 8p+6=2p-6 | | 9+2b=35 | | 2x+21=12+5x | | 4m+7m=4m-6+6m | | 4w-3w-1=8 | | -4s+14s=10 | | 13v+-6v=-14 | | 6a-4a+4=10 | | 8c-c+1=15 | | 8t+-20t+-11=17 | | 8t+-20t+11=17 | | 8t-20t-11=17 | | -2x+6=-11 | | 7-12=20-h | | 6/5=-2x | | 10+2y=y-10+5y | | 0.18(y-6)+0.02y=0.14y-1.5 | | -6/7u=-36 | | -5f=-7f-8 | | -2-13.8x=-8x-(6x+) | | 10-n=n-10 | | -28=-4/5v |

Equations solver categories